Meningkatkan Aktivitas dan Prestasi Belajar Matematika Materi Bangun Ruang Sisi Lengkung melalui Penerapan Model Pembelajaran Kooperatif Tipe STAD pada Siswa Kelas IX SMP LPMD Suka Maju Rambah - Nurbaiti Nurbaiti (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2020)
The purpose of this study was to describe the change in learning attitudes of students IX SMP LPMD Suka Maju Rambah in the 2017/2018 academic year regarding the increase in mathematics learning activities on curved side space building materials after learning through the application of the STAD cooperative learning model. The type of research used is a classroom action research, with a design used in two cycles. The population in this study were students of class IX SMP LPMD Suka Maju Rambah. Each cycle includes planning, action, observation, and reflection. The first cycle's learning outcomes showed that 26 students who completed learning whose score reached ≥ 75 were 26 students, or the percentage reached 78.78%. In the results of reflection in cycle I, it was found that the active involvement of students was 12 students, or the percentage was only 36.36%. Learning outcomes in cycle II, there was an increase in the number of students who completed, namely as many as 31 students or 93.93%, with 15.15%. Meanwhile, students' activeness in the second cycle also increased to 23 students, or 69.69%, with an increase of 33.33%. So it can be concluded that the application of the STAD learning model can improve activities and mathematics learning outcomes of students in grade IX at SMP LPMD Suka Maju, Rambah.